Performance Analysis of Filtered VHF Signals Captured by Lightning Interferometer System - Azmi N.A.I.; Ahmad M.R.; Esa M.R.M.; Sabri M.H.M.; Periannan D.; Seah B.Y.; Mohamad S.A.; Lu G.; Yusop N.; Ismail M.M.; Cooray V.; Alkahtani A.A.; et al. (Institute of Physics Publishing, 2023)
Antennas; Interferometers; Lightning; Lightning protection; Location; Signal processing; Azimuth and elevation angles; Cloud-to-ground flash; Cross-correlation algorithm; Interferometer systems; Narrow bipolar events; Performance analysis; Very high frequency; Vhf interferometers; Climate change